SURGICAL WOUND SUPPURATIVE COMPLICATIONS AFTER TENSION-FREE HERNIOPLASTY - M.KH. MALIKOV; F.B. BOKIEV; N.A. MAKHMADKULOVA; I.T. KHОMIDOV; O.M. KHUDOYDODOV; A.N. KAMOLOV (Avicenna Tajik State Medical University, 2022)
Objective: Analysis of surgical site suppurative complications after correction of large and giant ventral hernias. Methods: Various types of hernioplasty were performed on 220 patients with large and giant ventral hernias. Among the total number of patients, tension-free hernioplasty was performed in 123 patients, which accounted for 56% of the total number of patients. Various types of mesh implants were used, as well as different techniques of mesh placement in the area of the hernia ring. Results: Surgical site suppuration in the postoperative period occurred in 7 patients, which amounted to 5.6%. Partial removal of the mesh polymer implant was carried out only in one case. Timely diagnosis of the complications and adequate sanitation of the surgical site in 6 cases showed a good effect, and the implants did not necessitate removal. In one observation with necrosis of the edges of the wound and suppuration of the surgical site, after partial removal of the implant, a hernia recurrence was noted in the area of the removed mesh. In 6 other cases, there was no recurrence of the pathology during the long-term follow-up. Conclusion: Surgical site suppurative inflammation in the postoperative period, negatively affecting the outcome of the operation, can contribute to hernia recurrence. Timely diagnosis of complications and adequate sanitation of surgical site in most cases give satisfactory results.